(untitled) (Research, Society and Development, 2024)
Introduction: Chronic pain is characterized by the persistence of nociceptive stimulation, which loses its physiological purpose and remains after healing or in the absence of disease. Some factors are associated with its occurrence, such as age, so that, in the coming years, an increase in the prevalence of chronic pain is expected. Thus, in view of the potential harm caused by the use of medications, it is extremely necessary to search for non-pharmacological alternatives for the treatment of such pain and, in this sense, this work aims to analyze such alternatives, as well as their effects and the effectiveness of each one of them. Methodology: This is an integrative review about non-pharmacological treatment in the management of chronic pain. Data from the Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed) databases were used, from the intersection of the descriptors “chronic pain”, “musculoskeletal pain”, “Mindfulness” and “cognitive-behavioral therapy”, to answer the question formulated through the PICO strategy. Results and Discussion: The prevalence, costs, absenteeism and reduced productivity are consequences of chronic pain that made it a public health problem. For the most part, the use of drugs is the treatment of choice, resulting in an epidemic of opioid dependence. However, the positive results for alternative treatments, such as mindfulness therapy, cognitive-behavioral therapy, physical activity, laser therapy and acupuncture, demonstrate the possibility of complementing or replacing pharmacological treatment. Conclusion: The chronicity of pain generates consequences and negative feelings. Therefore, more studies are needed on non-pharmacological treatments so that patients have effective and safe alternatives to treat and live with pain.